Osteoradionecrosis in the Current Era of Radiation Treatment. (2nd January 2022) - Patel, Vinod; Fenlon, Michael; Silvio, Lucy Di; McGurk, Mark
Abstract : Osteoradionecrosis (ORN) is a late complication of radiotherapy treatment for head and neck cancer. In the past two decades there have been significant changes in the mode by which radiation is delivered and it was assumed this would lead to a reduction, or even elimination, of this complication. Paradoxically, ORN rates may have risen. This article provides a summary of the current understanding and approach to ORN. CPD/Clinical Relevance: Those who have had radiotherapy carry a life-long risk of developing osteoradionecrosis, and it is important that the dental team are aware of this.